The Effect of Good Corporate Governance Mechanism On The Financial Performance of Banking Companies Listed In Stock Exchange Indonesia 2012-2016 - Desi Pipian Pujakusum (Pusat P2M Politeknik Negeri Batam, 2019)
This study aims to examine the effect of good corporate governance mechanism on the financial performance of banking companies listed on the Indonesian Stock Exchange 2012-2016 period. The corporate governance mechanism is proxied by the size of the board of directors, the size of the board of commissioners, audit committee size, the board of director's education, and the board of commissioner’s education. The company's financial performance is proxied by return on assets (ROA). Samples were taken by using purposive sampling. The total number of samples used in this study amounted to 180 research samples. This study was tested with SPSS 20 program. Data analysis technique used in this research is simple regression analysis. The results showed that the size of the board of directors, the size of the board of commissioners, and audit comitee size have a significant effect on return on assets. These three factors have a significant effect on return on assets, while the board of commissioners education and the board of director's education have no significant effect on return on assets.